MicroRNA as Potential Biomarkers of Platelet Function on Antiplatelet Therapy: A Review - Czajka, Pamela; Fitas, Alex; Jakubik, Daniel; Eyileten, Ceren; Gasecka, Aleksandra; Wicik, Zofia; Siller-Matula, Jolanta M.; Filipiak, Krzysztof J.; Postula, Marek (Frontiers in Physiology, 2021)
MicroRNAs (miRNAs) are small, noncoding RNAs, able to regulate cellular functions by specificgene modifications. Platelets are the major source for circulating miRNAs, with significant regulatory potential on cardiovascular pathophysiology. MiRNAs have been shown to modify the expression of platelet proteins influencing platelet reactivity. Circulating miRNAs can be determined from plasma, serum, or whole blood, and they can be used as diagnostic and prognostic biomarkers of high platelet reactivity during antiplatelet therapy as well as novel therapeutic targets in cardiovascular diseases. Herein, we review diagnostic and prognostic value of miRNAs related to platelet reactivity based on human studies, presenting its interindividual variability as well as the substantial role of genetics. Furthermore, we discuss antiplatelet treatment in the context of miRNAs alterations related to pathways associated with drug response.